Hypoxia and its possible relationship with endometrial receptivity in adenomyosis: a preliminary study - Song Guo; Di Zhang; Xiaowei Lu; Qian Zhang; Ruihuan Gu; Binghui Sun; Yijuan Sun (BMC, 2021)
Abstract Background Adenomyosis (AM) is an important cause of female infertility. However, the underlying mechanism remains unclear. This report describes a preliminary study of hypoxia and its possible association with endometrial receptivity in AM. Methods The study was divided into in vitro and in vivo experiments. In vitro, expression levels of the endometrial receptivity markers HOXA10 and HOXA11 in the implantation period were examined using real-time PCR and western blotting. Endometrial expression of hypoxia-inducible factor (HIF)-1α, HIF-2α, and HIF-3α was determined using immunohistochemistry. In vivo, using an AM mouse model established by oral administration of tamoxifen, we inhibited expression of HIF-2α using an HIF-2α antagonist (PT2399; 30 mg/kg body weight, twice daily by oral gavage for 2 days) and then examined expression levels of Hoxa10 and Hoxa11 using real-time PCR and western blotting. Results Endometrial mRNA and protein expression levels of HOXA10 and HOXA11 were significantly lower in patients with AM than in control patients. Expression of HIF-2α was significantly higher in the AM group than in the control group, whereas that of HIF-1α and HIF-3α was equivalent in both groups. In vivo analysis showed that administration of the HIF-2α antagonist resulted in increased expression of Hoxa10 and Hoxa11 at both the mRNA and protein levels in AM model mice. Conclusions HIF-2α overexpression may be one reason for decreased endometrial receptivity in AM. The current findings provide insight into HIF-2α-mediated AM-related infertility and suggest that PT2399 has potential as a treatment for AM. Trial registration This trial was retrospectively registered.